The importance of rehabilitating tourism infra-structure for local development in Tizi Ouzou - Chichoune Malika; Souiher Khalil; Belguesmia Sabiha; Rezzaz Mohammed Abdessamed; Madoui Abdelaziz (Glasnik Srpskog Geografskog Društva)
Algeria's diverse natural landscape attracts tourists for coastal and marine exploration, mountain, desert adventures and cultural experiences. The Yakouren region in the Atlas Mountains is an ideal destination for mountain tourism, with breathtaking scenery, enticing peaks and popular activities such as climbing, camping and entertainment, as well as skiing competitions in winter. To further the development of tourism in the Yakouren region, it is imperative to restore critical facilities such as hotels and historic residences. This study focuses on the rehabilitation of a neglected hotel and its surroundings in order to rehabilitee the local tourism industry and raise its profile. The ultimate goal is to create a sustainable and enduring attraction that will enchant local and international visitors. The article highlights the importance of conducting a thorough financial feasibility study to confirm the positive returns of the project and to stimulate economic growth in the area and throughout Algeria. This can be enhanced by conducting a questionnaire to study the factors influencing regional tourism development, using statistical indicators such as Cronbach's alpha coefficient, Spearman's correlation, and linear regression. These methods can help facilitate a better understanding of the research results in areas with tourist destinations that require infrastructure activation.